TUGAS DAN FUNGSI DPRD PROVINSI KALIMANTAN TIMUR DALAM PEMBANGUNAN DAERAH KALIMANTAN TIMUR MENURUT UNDANG-UNDANG NOMOR 23 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH - Rani Sundari (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
ABSTRACT            The implementation of people's sovereignty based on democracy which is led by wisdom in consultation / representation, it is necessary to realize people's consultative institutions and regional people's representative institutions that are able to fight for democratic values and can absorb and fight for the aspirations of the people, including regional interests, in accordance with the demands of the development of people's lives nation and state.            DPRD of East Kalimantan Province is one of the institutions representing all levels of society in government. However, based on observations made by researchers, in carrying out their duties and functions as representatives of the people, the DPRD of East Kalimantan Province has not been able to contribute so optimally to the interests of the community in this matter the procurement of regional facilities and infrastructure, because the regional government of East Kalimantan Province is only more focused in regional development and development.            Based on the background described above, the authors formulated the problem as follows: (1) How is the implementation of the duties and functions of the East Kalimantan Provincial Parliament in the development of the East Kalimantan area according to Law Number 23 of 2014 concerning Regional Government? (2) What are the obstacles in the implementation of the duties and functions of the East Kalimantan Provincial Parliament in the development of the East Kalimantan region according to Law Number 23 of 2014 concerning Regional Government?             So that it can be concluded (1) Development carried out in rural / urban districts can run well if DPRD members can carry out their duties and functions of supervision properly and decisively against violators and the participation of rural / urban districts and communities to participate in overseeing the course of development. Supervision as a whole process of assessing the object of the inspection activity, with the aim that planning and implementation goes according to its function, and successfully achieve what has been determined. The purpose of supervision is directed so that the implementation of general tasks and development in rural / urban districts can run according to government plans and policies so that they can achieve the goals in an effective, effective and efficient way to the achievement of development objectives depends on the effectiveness of supervision carried out by the DPRD and the participation and people's aspirations. (2) There are several factors that influence the weak implementation of the supervisory function of the members of the DPRD of East Kalimantan Province, including: organizational factors, factors of political background of members, and factors of knowledge about supervision techniques from members. Keywords: Duties & Functions of DPRD, Regional Development, Regional Government